Production of flavouring agent from shrimp heads - Teerasuntonwat, Patcharee (2013)
A flavouring agent was prepared from shrimp heads by extraction of nitrogenous compounds with water, sodium chloride, hydrochloric acid, sodium hydroxide, bromelain, papain and neutrase. The approriate conditions of extraction were based on total solids, formaldehyde nitrogen, soluble protein contents and sensory evaluation scores. Shrimp flavour extract was dried using dextrin, dextrose or sodium chloride as binders. Bromelain was found to be the most promising extracting medium. The appropriate conditions were 0.25 percent bromelain, pH 6, for 5 hrs at 50 degree C using sodium chloride as the binder. The free amino acid compositions of shrimp flavour powders prepared with water and bromelain were similar, but the total amino acid content in shrimp flavour extracted with enzyme was about 2,5-fold higher. The major free amino acids in both flavouring agents were alanine, glycine and arginine. The major amino acids in the acid hydrolysate of the shrimp flavour powder were glutamic acid, glycine and alanine. Sensory evaluation of an aqueous solution of the preferred flavouring difference (P less than 0.05) but shrimp flavoured crackers containing 2 percent krill extract had a higher preference score than those prepared with 2 percent of the shrimp head extract.